The Effect of LDPE Microplastics on Soil Metabolic Activities and Microbial Community Profile - Yang K.M. (2023)
Almost half a million tons of plastic wastes are produced every year and it is accumulating in the environment. However, there is a lack of understanding of their potential influence on soil metabolic activities and microbial diversity. Therefore, a soil microcosm experiment was conducted to determine the influence of microplastics (MPs) (size ~ 500 µm) on soil microbial activities with various concentrations of low-density polyethylene MPs (0, 0.5, 1, and 2% w/w). PCR-DGGE was applied to determine the influence of MPs on soil microbial community structure. This study revealed that MPs with concentration > 1% could affect soil microbial metabolic activities and bacterial community profile with incubation time. Soil catalase (CAT), dehydrogenase (DHA), and invertase (INV) activities were determined. Soil DHA and INV activities decreased over time. No clear trend or pattern was observed in DHA activities. Catalase activity increased with the concentration of microplastics over time. Furthermore, DGGE analysis showed that LDPE microplastics >1% pose a powerful selection pressure on soil microbial community structure. In particular, microbial communities associated with hydrocarbon degradation were enriched (Pseudomonas, Bacillus, and Sphinogomonas species) in soil contaminated with a high concentration of LDPE microplastics. These findings add to the growing body of evidence on the complex interference of MPs on the soil ecosystem. The influence of MPs in microbial diversity and activities is a significant environmental concern as it may also disturb N and P nutrient cycling, which needs further investigation.